Strategi Pemasaran dan Peran Kiai dalam Peningkatan Jumlah Nasabah BMT Sunan Drajat Lamongan - Akhmad Sirojudin Munir (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study aims to comprehend the marketing plan put in place by BMT Sunan Drajat Lamongan and the part Kiai plays in boosting the number of customers. The methodology used is qualitative, with a case study approach. Data is collected through interviews, observations, and documentation. Research results showed that BMT Sunan Drajat Lamongan implemented various marketing strategies, including digital marketing, direct promotion, and public relations. Kh. Abdul Ghofur, as a key figure in this BMT, has played a key role in building confidence and raising public awareness of the services offered. His leadership in providing Shariah financial education was also an important factor in the increase in the number of clients. This research provides new insights into how a combination of effective marketing strategies and figure roles can boost customer growth in the Sharia loan sector.